The Decision to Grant or Deny Parole: A Study of Parole Criteria in Law and Practice - Robert O. Dawson (Washington University Law Quarterly, 1966)
The purpose of this Article is to report the results of field research into the exercise of discretion by parole boards in Kansas, Michigan, and Wisconsin, and to suggest some of the difficulties likely to face those who undertake the task of effectively controlling parole board discretion.
Keywords: Parole